2002
DOI: 10.1097/00001756-200203250-00008
|View full text |Cite
|
Sign up to set email alerts
|

BK channel blockers inhibit potassium-induced proliferation of human astrocytoma cells

Abstract: The functional role of BK channels, which are consistently expressed in glioma cells, is not clear. Here we show that the BK channels are regularly active in human 1321N1 astrocytoma cells at physiological membrane potentials. The proliferation of the cells at the physiological external [K+] of 5 mM is compared with that at the elevated external [K+] of 20 mM, simulating the situation in rapidly growing, necrotic tumours in vivo. High extracellular [K+] in the range 10-30 mM significantly increases the prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 22 publications
4
40
0
Order By: Relevance
“…The oncogenic role of KCNMA1 found in this study is in line with the previously reported growth inhibition of human astrocytoma by IBTX (Basrai et al, 2002;Weaver et al, 2004). Interestingly, the intermediate conductance K þ channel (IK) rather than KCNMA1 has been proposed to be important for PC-3 and LNCaP cells by Parihar et al (2003).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The oncogenic role of KCNMA1 found in this study is in line with the previously reported growth inhibition of human astrocytoma by IBTX (Basrai et al, 2002;Weaver et al, 2004). Interestingly, the intermediate conductance K þ channel (IK) rather than KCNMA1 has been proposed to be important for PC-3 and LNCaP cells by Parihar et al (2003).…”
Section: Discussionsupporting
confidence: 90%
“…For example, BK channel activation has been shown to drive tumor cell proliferation in astrocytoma (Basrai et al, 2002). Moreover, a previous report has suggested a role of potassium channels for the proliferation of prostate cancer (Van Coppenolle et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…3B, 4), our study demonstrated that quercetin-evoked hyperpolarization is due to K + efflux through BKCa activation and may eventually trigger apoptosis or inhibition of tumor cell proliferation, at least in bladder cancer cells. The involvement of BKCa in cell growth however is still controversial [26,27], although there is a close link between BKCa channels and cell proliferation [31,32] and several published data have shown involvement of BKCa channels in tumor growth in various malignant cell lines [33][34][35][36]. Abdullaev and colleagues [26] suggested that the BKCa channel lacked participation in cell proliferation in glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro studies showed that disrupted BK channel functional activity inhibits glioma cell proliferation (33,34) and migration (35,36). Earlier, we showed that prolonged activation of BK channels of T9 or U251 gliomas in vitro causes cell swelling and eventually leads to paraptosis (7,8).…”
Section: Discussionmentioning
confidence: 91%